2013
DOI: 10.1037/a0029907
|View full text |Cite
|
Sign up to set email alerts
|

Factorial, convergent, and discriminant validity of timss math and science motivation measures: A comparison of Arab and Anglo-Saxon countries.

Abstract: For the international Trends in International Mathematics and Science Study (TIMSS2007) math and science motivation scales (self-concept, positive affect, and value), we evaluated the psychometric properties (factor structure, method effects, gender differences, and convergent and discriminant validity) in 4 Arab-speaking countries (Saudi Arabia, Jordan, Oman, and Egypt) and 4 English-speaking Anglo-Saxon countries (United States, England, Australia, and Scotland). In this article, we also highlight methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
149
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(173 citation statements)
references
References 112 publications
18
149
1
5
Order By: Relevance
“…In the Arabic world, consistent with the TIMSS findings (see also, Marsh et al 2013;Ayalon and Livneh 2013), studies have found higher achievements favoring girls in Middle Eastern Arabic-speaking countries (e.g., Abu-Hilal 2001;Fryer and Levitt 2010;Mullis et al 2012) but favoring boys in Arabic countries in Africa (Ayalon and Livneh 2013). A possible explanation for the Middle Eastern Arabic-speaking scenario is that girls are more restricted to their homes than boys, and therefore they have more time to focus on their schoolwork than boys (Abu-Hilal 2001).…”
Section: Gender and Educational Aspirationssupporting
confidence: 77%
See 3 more Smart Citations
“…In the Arabic world, consistent with the TIMSS findings (see also, Marsh et al 2013;Ayalon and Livneh 2013), studies have found higher achievements favoring girls in Middle Eastern Arabic-speaking countries (e.g., Abu-Hilal 2001;Fryer and Levitt 2010;Mullis et al 2012) but favoring boys in Arabic countries in Africa (Ayalon and Livneh 2013). A possible explanation for the Middle Eastern Arabic-speaking scenario is that girls are more restricted to their homes than boys, and therefore they have more time to focus on their schoolwork than boys (Abu-Hilal 2001).…”
Section: Gender and Educational Aspirationssupporting
confidence: 77%
“…Studies across different countries have consistently identified a cultural dimension for gender differences in mathematicsrelated affect and performance (Hyde and Mertz 2009;Forgasz et al 2015) with studies indicating that gender significantly influences students' mathematics self-concept, mathematics self-confidence, and the perceived usefulness of mathematics (e.g., Belcher et al 2006). For instance, studies have reported lower mathematics confidence, less liking for mathematics, a lower mathematics self-concept, and a lower value for mathematics for girls in science and mathematics tasks (Frenzel et al 2010;Hyde et al 1990;Else-Quest et al 2010;Marsh et al 2013;OECD 2015;Nagy et al 2010;Watt 2004;Watt et al 2012). Moreover, other studies have consistently shown gender differences favoring males in their mathematics ability even when there is no evidence of any achievement differences between the sexes (Frenzel et al 2010;Nagy et al 2010;Watt 2004).…”
Section: Gender and Educational Aspirationsmentioning
confidence: 96%
See 2 more Smart Citations
“…In this context, it might not only be worthwhile to study the math and verbal domains separately but to also investigate different domains simultaneously . Furthermore, since only self-concept operationalized as students' perceptions of competence was considered, further variables for students' self-perceptions should be addressed such as affect self-perceptions (Arens et al, 2011;Marsh et al, 2013). Finally, beyond achievement, it might be worthwhile to take a broader range of outcome variables such as goal orientations , effort (Trautwein, Lüdtke, Schnyder, & Niggli, 2006) or emotions (Pekrun, 2006) into account.…”
Section: Discussionmentioning
confidence: 99%